“PERINGATAN DARURAT” AS A CANCEL CULTURE MOVEMENT THROUGH SOCIAL MEDIA IN INDONESIA - Wempi, Jefri Audi; Chrisdina, Chrisdina; Rully, Rully (Nyimak: Journal of Communication, 2025)
At that time, the Indonesian government was organizing regional elections, part of the ongoing general election process following the presidential and legislative elections. In a short period, a public movement emerged to reject and cancel the Draft Law (RUU) proposed by the Indonesian Parliament, following the Constitutional Court's ruling on presidential nomination thresholds and political party participation in elections. The "Cancel Culture" movement, known as the "Emergency Alert," quickly gained momentum and was carried out by various groups across Indonesia. It culminated in massive demonstrations involving diverse communities. This study’s key question is how the "Emergency Alert" movement, through social media, managed to oppose the regional election bill so quickly and effectively, motivating people to participate in both online and physical protests. The research aims to understand the content and platforms used in social media to shape public participation, and how the characteristics of new media triggered rapid and widespread engagement. Using new media, social media, and cancel culture theories, this qualitative research with a constructivist framework found that new media characteristics—interactivity, friendliness, richness, autonomy, playfulness, privacy, and personalization—were crucial in mobilizing support for the "Emergency Alert" movement.Keywords: Digital Political Activism, Cancel Culture, Emergency AlertABSTRAKPemerintah Indonesia saat itu tengah menyelenggarakan pemilihan kepala daerah, bagian dari proses pemilihan umum yang sedang berlangsung setelah pemilihan presiden dan legislatif. Dalam waktu yang singkat, muncul gerakan masyarakat untuk menolak dan membatalkan Rancangan Undang-Undang (RUU) yang diajukan oleh DPR RI, menyusul Putusan Mahkamah Konstitusi ketentuan mengenai ambang batas pencalonan presiden dan partisipasi partai politik dalam pemilu. Gerakan "cancel culture" yang dikenal sebagai "Peringatan Darurat" dengan cepat mendapatkan momentum dan dilakukan oleh berbagai kelompok di seluruh Indonesia. Puncaknya adalah demonstrasi besar-besaran yang melibatkan berbagai komunitas. Pertanyaan utama dari penelitian ini adalah bagaimana gerakan "Peringatan Darurat" melalui media sosial berhasil menentang RUU PILKADA dengan begitu cepat dan efektif, memotivasi orang untuk berpartisipasi dalam protes fisik dan online. Penelitian ini berupaya memahami konten dan platform media sosial yang digunakan untuk membentuk partisipasi publik dalam gerakan ini, dan bagaimana karakteristik media baru memicu keterlibatan yang cepat dan meluas. Penelitian ini menggunakan teori media baru, media sosial, dan budaya pembatalan, dengan menggunakan pendekatan kualitatif dengan kerangka konstruktivis. Temuan penelitian menunjukkan bahwa karakteristik media baru—interaktivitas, keramahan, kekayaan media, otonomi, keceriaan, privasi, dan personalisasi—sangat penting dalam memobilisasi dukungan untuk gerakan “Peringatan Darurat”.Kata Kunci:  Aktivitas Politik Digital, Cancel Culture, Peringatan Darurat